Rekonstruksi Nalar Fikih dalam Perspektif ‎Studi Islam Kontemporer ‎(Pemikiran Jamal Al-Banna)‎ - Mukhammad Zamzami (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2008)
Beside known as a brother of the Hasan al-Banna of Ikhwan al-Muslim, Jamal al-Banna is also a controversial yet respected scholar of Islam. He is a prolific writer with 100 book titles bearing his name. He writes on Islamic theme as well other themes such as democracy and politics. He also engages in civil society activities. One of his thoughts is about reforming classical Islamic law which he elucidates in one of his book entitled Nahw Fiqh Jadid; (Towards New Islamic Law). In that book he asserts that medieval legal methodology, especially about istidlal (interpretation) is no longer applicable nowadays.